Androgen interacts with exercise through the mTOR pathway to induce skeletal muscle hypertrophy - Zeng, Fanxing; Zhao, Hua; Liao, Jingwen (Biology of Sport, 2017)
This study was designed to investigate the effects of exogenous androgen and resistance exercise on skeletal muscle hypertrophy and the role of the mammalian target of rapamycin (mTOR) signalling during the process. A total of 24 male Sprague-Dawley rats were randomly assigned to sham operation and dihydrotestosterone (DHT) implantation groups with subgroups subjected to sedentary conditions or resistance exercise (SHAM+SED, SHAM+EX, DHT+SED, and DHT+EX). The experimental procedure lasted for 10 days. The mRNA expression of androgen receptor (AR) and insulin-like growth factor I (IGF-I), the expression of myosin heavy chain (MHC), as well as the phosphorylation statuses of AR, mTOR, p70 ribosomal S6 kinase (p70S6K), and eukaryotic translation initiation factor 4E-binding protein 1 (4EBP1) were determined in the white gastrocnemius muscle. The cross sectional area and wet mass of the muscle were also measured. The cross sectional area and MHC expression were significantly higher in SHAM+EX, DHT+SED, and DHT+EX than in SHAM+SED. There was no significant difference among groups in muscle mass. The mRNA expression of AR and IGF-I and the phosphorylation of mTOR, p70S6K, and 4EBP1 were significantly increased in DHT+SED and SHAM+EX and were significantly enhanced in DHT+EX compared with either DHT or exercise alone. These data show that DHT causes hypertrophy in skeletal muscle and that exercise has a synergistic effect on DHT-induced hypertrophy. Exercise enhances androgen-induced rapid anabolic action, which involves activation of the mTOR pathway.